2019
DOI: 10.1055/s-0039-1681080
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pathologic Fractures Around the Hip: Part 1–Femur

Abstract: Evaluation and management of suspected pathologic fractures, secondary to metastatic disease, require a comprehensive understanding of the underlying disease process and a multidisciplinary treatment approach. Recognition of a pathologic fracture can be challenging, and the diagnosis today remains often missed, but is necessary for appropriate care. The incidence of cancer in the United States is on the rise, and with advances in medical and surgical care the prevalence of cancer is increasing as well. This wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Mirels criteria study showed fair to moderate agreement between authors when using the Mirels score to quantify the need for fixation in pathological and diseased bone. (7) We present four cases of metastasis to the proximal femur in patients managed with Proximal femoral replacements.…”
Section: Introductionmentioning
confidence: 99%
“…Mirels criteria study showed fair to moderate agreement between authors when using the Mirels score to quantify the need for fixation in pathological and diseased bone. (7) We present four cases of metastasis to the proximal femur in patients managed with Proximal femoral replacements.…”
Section: Introductionmentioning
confidence: 99%